SPECTACLE AS A FORM OF MASS COMMUNICATION IN THE CONTEXT OF DIVERSITY OF COMMUNICATION MEANS - Абисова, М. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article is devoted to the analysis of communicative characteristics of the spectacle under circumstances of total visualization in the post-modern society